Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 60292 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Senecio L.", "HasGeospatialIssue is false", "Geometry POLYGON((-10.63 53.38,-10.63 62.61,16.92 62.61,16.92 53.38,-10.63 53.38))" ] } The dataset includes 60292 records from 94 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0083038-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences